Peranan Petugas Pengamanan Laki-Laki di Lembaga Pemasyarakatan Perempuan (Studi Lembaga Pemasyarakatan Perempuan Kelas II A Tenggarong) - Andi Pratama; Suheflihusnaini Ashady (Juridische : Jurnal Penelitian Hukum, 2024)
In carrying out its functions, the Women's Correctional Institution faces challenges related to the role of male security officers who work in it. The limited number of male security officers is a sensitive and complex issue that affects aspects of security, privacy and the human rights of women. In conducting this research the author used empirical research methods with juridical, conceptual and sociological approaches. The research results show that one important aspect in securing women's prisons is the availability of male security officers because they have greater physical strength, which can help in controlling situations that may require physical force. A lack of male security officers can make women's prisons more vulnerable to conflict, violence or chaos that is difficult to control. The implementation of security activities carried out at the Tenggarong Class II A Women's Correctional Institution is slightly different from prisons in general, especially in securing the main door. Firstly, there are no clear legal regulations or regulations regarding standards regarding the minimum number of male security officers in women's prisons and secondly, the lack of male security officers in women's prisons shows that there is a gap in the understanding and implementation of regulations relating to the number and placement. officer. So this condition needs to be immediately addressed through revision of regulations that are more comprehensive and responsive to the needs of the Women's Correctional Institution for male security officers.